VIGNETTE ILLUSTRATION WORK ABOUT THE MEANING OF MACAPAT SONGS - Ibnu Sina; Fiyanto, Arif (Universitas Negeri Semarang, 2025)
Indonesia is a country rich in ethnic diversity, cultures, and customs. A large portion of its population is dominated by the Javanese ethnic group. However, many Javanese people today lack knowledge about their own customs, traditions, and cultural heritage, such as the traditional tembang macapat. This form of cultural expression should be preserved, as it contains a wealth of moral messages and noble values about human life. This paper aims to create vignette illustration works based on tembang macapat as a means of building public appreciation for Javanese culture and tradition through art exhibitions. In order to present visually appealing vignette illustrations of tembang macapat, the author followed several creative stages, including concept development and visualization, which involve sketching, outlining, adding details and accents, shading, and final touches. The author hopes that this vignette illustration work, which highlights the meaning behind tembang macapat, will be beneficial and serve as inspiration for many. In creating art, one should explore more with ideas/concepts, media, and techniques. It is also hoped that the outcomes of this work can contribute positively to the university, students, and art appreciators in the future.